2017
DOI: 10.1371/journal.pone.0177023
|View full text |Cite
|
Sign up to set email alerts
|

Positive association between ALDH2 rs671 polymorphism and essential hypertension: A case-control study and meta-analysis

Abstract: Background and objectiveSeveral studies have been conducted to examine the association between aldehyde dehydrogenase 2 family (ALDH2) rs671 polymorphism and essential hypertension (EH). However, the results remain inconsistent. This study aimed to clarify the association between ALDH2 rs671 polymorphism and EH susceptibility.MethodsOne thousand and ninety-four cases and 1236 controls who were ethnic Han Chinese were collected for this population-based case-control study. A meta-analysis was performed to calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 32 publications
(31 reference statements)
1
20
0
Order By: Relevance
“…Finally, 22 articles (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Iwai et al, 2004 ; Hui et al, 2007 ; Hasi et al, 2011 ; Feng et al, 2012 ; Lv et al, 2013 ; Nakagawa et al, 2013 ; Wang et al, 2013 ; Wu et al, 2013 , 2017 ; Yokoyama et al, 2013 ; Zhang et al, 2013 , 2016 , 2018 ; Isomura et al, 2015 ; Jing et al, 2015 ; Ota et al, 2016 ; Li et al, 2017 ; Ma et al, 2017 ; Du, 2018 ) met the preset inclusion criteria. Among these articles, 20 (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Iwai et al, 2004 ; Hui et al, 2007 ; Hasi et al, 2011 ; Feng et al, 2012 ; Lv et al, 2013 ; Nakagawa et al, 2013 ; Wang et al, 2013 ; Wu et al, 2013 , 2017 ; Yokoyama et al, 2013 ; Jing et al, 2015 ; Ota et al, 2016 ; Zhang et al, 2016 , 2018 ; Li et al, 2017 ; Ma et al, 2017 ; Du, 2018 ) assessed the association between the rs671 polymorphism and EH risk in 30 individual studies (11,051 hypertensive patients and 15,926 normotensive controls), and 8 (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Wang et al, 2013 ; Zhang et al, 2013 ; Isomura et al, 2015 ; Ota et al, 2016 ; Li et al, 2017 ) assessed the association between the rs671 polymorphism and BP levels in 12 individual studies (20,512 subjects). The baseline characteristics of all included articles are summarized in Table 1 (for EH) and Table 2 (for BP).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 22 articles (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Iwai et al, 2004 ; Hui et al, 2007 ; Hasi et al, 2011 ; Feng et al, 2012 ; Lv et al, 2013 ; Nakagawa et al, 2013 ; Wang et al, 2013 ; Wu et al, 2013 , 2017 ; Yokoyama et al, 2013 ; Zhang et al, 2013 , 2016 , 2018 ; Isomura et al, 2015 ; Jing et al, 2015 ; Ota et al, 2016 ; Li et al, 2017 ; Ma et al, 2017 ; Du, 2018 ) met the preset inclusion criteria. Among these articles, 20 (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Iwai et al, 2004 ; Hui et al, 2007 ; Hasi et al, 2011 ; Feng et al, 2012 ; Lv et al, 2013 ; Nakagawa et al, 2013 ; Wang et al, 2013 ; Wu et al, 2013 , 2017 ; Yokoyama et al, 2013 ; Jing et al, 2015 ; Ota et al, 2016 ; Zhang et al, 2016 , 2018 ; Li et al, 2017 ; Ma et al, 2017 ; Du, 2018 ) assessed the association between the rs671 polymorphism and EH risk in 30 individual studies (11,051 hypertensive patients and 15,926 normotensive controls), and 8 (Takagi et al, 2001 ; Amamoto et al, 2002 ; Saito et al, 2003 ; Wang et al, 2013 ; Zhang et al, 2013 ; Isomura et al, 2015 ; Ota et al, 2016 ; Li et al, 2017 ) assessed the association between the rs671 polymorphism and BP levels in 12 individual studies (20,512 subjects). The baseline characteristics of all included articles are summarized in Table 1 (for EH) and Table 2 (for BP).…”
Section: Resultsmentioning
confidence: 99%
“…Whether there is a relationship between the ALDH-2 rs671 polymorphism and hypertension remains unclear. Even previous meta-analysis studies on this issue have drawn different conclusions, and only focused on the association between ALDH-2 and essential hypertension risk (Jia et al, 2015 ; Li et al, 2017 ; Wu et al, 2017 ). In order to conclude the influence of the ALDH-2 rs671 polymorphism on hypertension, we performed a more comprehensive systematic review and meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, several studies suggested that the rs671 L genotype was a protective factor in hypertension development. Wu Y 43 conducted case-control study and meta-analysis and indicated a decreased risk of hypertensive risk in AA/AG genotype. Zhang SY 18 found that the rs671 GG genotype was associated with an increased risk of hypertension compared with the AG/AA genotypes, especially in men and this association was independent of alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH2 rs671 polymorphism genotyping was performed using polymerase chain reaction-ligase detection reaction (PCR-LDR) method (Generay Biotech Company, Shanghai, China). Primer sequences and reaction conditions used were described previously [ 17 ]. For quality control, we randomly chose 10% of the samples to re-genotype, and the concordance was 100%.…”
Section: Methodsmentioning
confidence: 99%
“…ALDH2 rs671 polymorphism exists mainly in the East Asian population, whereas it is quite rare in Caucasian and African population [ 12 ]. Accumulating evidence suggests that the ALDH2 rs671 polymorphism is associated with the risk of CAD in Asian population [ 8 , 13 16 ], and the mechanisms may relate to the effect of ALDH2 rs671 polymorphism on hypertension [ 17 19 ], dyslipidemia [ 13 , 20 , 21 ], and endothelial asymmetric dimethylarginine (ADMA) levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%